LIFE STYLE IN CHILDREN FROM PUBLIC AND PRIVATE SCHOOL IN THE CITY OF GOIANÉSIA-GO. (Fiep Bulletin - online, 2013)
A healthy life style is characterized by a balance between what is eaten (feeding) and what is spent (physical activity). The study had as a purpose to discuss, through the comparison between two schools, the level of physical activity and food habits of these children. The research is characterized as a transversal kind of descriptive quantitative character. It was realized in Goianésia-Go wih 178 children from both sexes from the elementary school from 2nd to 5th year, in the group age of 6 to 11 years old, from the morning and afternoon shifts of the Escola Municipal Evangélica Monte Moriá (Municipal Gospel School Monte Moriá) of the Colégio Decisão (Decisão High School), using a questionnaire to collect data. There weren't significant difference in the results when compared the food habits from public to private schools, and regarding the sexes, there weren't also significant difference. Concerning the level of physical activity, the results were 20,7% and 29,1% for the public and private schools, classified as sedentary; 18,5% and 32,6% classified as insufficiently active; but moderately active were 19,6% and 31,4%, and classified as active were 41,3% and only 7% private school, in where we could find a significant difference (p < 0,000) between the schools. The study concluded that, through the results of this research, it was possible to identify that the students from the public school are active and, the students from the private school are sedentary, and both schools show insufficiently feeding to fulfil the needs of the body.
Keywords: life style; childrens; schools